1995
DOI: 10.1002/jrs.1250261206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pt—Cl force constants on the Raman lineshapes in Pt35Cl/37Cl chains

Abstract: The influence of the "CI/37CI isotopic disorder of natural chlorine on the Raman and infrared lineshapes of the vibrational modes in PtCl chains was calculated as a function of the interionic force constants in a one-dimensional model. It is shown that the fine structure of the Raman line is strongly dependent of the Pt3+'-CI and Pt3-d-CI force constants, and so it can he used to estimate the charge disproportion 6. From the case of [ Pt(en),] I Pt(en),Cl,] (CIO,), it appears that the description of the high-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Prior modeling of this fine structure indicated that these peaks correspond to vibrations that extend over several unit cells of the material with different statistical isotopic patterns. [22][23][24][25] Similarly, the first overtone fine structure also corresponds to a set of isotopically mixed vibrations that may extend over more than one PtCl 2 unit. 25 At the second overtone, a simple three-peak pattern is observed, and the peak heights are in the ratio of ≈1:6.5:8.7.…”
Section: Resultsmentioning
confidence: 99%
“…Prior modeling of this fine structure indicated that these peaks correspond to vibrations that extend over several unit cells of the material with different statistical isotopic patterns. [22][23][24][25] Similarly, the first overtone fine structure also corresponds to a set of isotopically mixed vibrations that may extend over more than one PtCl 2 unit. 25 At the second overtone, a simple three-peak pattern is observed, and the peak heights are in the ratio of ≈1:6.5:8.7.…”
Section: Resultsmentioning
confidence: 99%
“…The main interest of these structures comes from the presence of the quasi-one-dimensional linear and straight infinite chains of alternating metal (M) and halogen (X) atoms, the metallic ions along the chains being alternately in the oxidation states M 3-~ and M3+~; the charge disproportion 3 varies from 0 to 1 so that the MX chains can be considered as CDW (chargedensity wave) systems (Baeriswyl & Bishop, 1988). One-dimensional models successfully described the electronic properties of the chains (Huang, Batistic & Bishop, 1993) as well as the longitudinal vibrational properties (Bulou, Donohoe & Swanson, 1991), even in the case of the isotopically disordered 35C1/37C1 system (Love, Worl, Donohoe, Huckett & Swanson, 1992;Bardeau, Bulou & Swanson, 1995). Their interest is also due to the fact that valence defects (polarons, bipolarons etc.…”
Section: Introductionmentioning
confidence: 99%